Prevalence of De Quervain’s Tenosynovitis among Teenage Mobile Users: A Cross-Sectional Study - Mohammad Rehan Asad; Ritu Kumar Ahmad; Husam A. Almalki; Khalid M. Alkhathami; Bijad Alqahtani (Journal of Pharmacy and Bioallied Sciences)
Background: This study aimed to demonstrate the association between smartphone use and De Quervain’s syndrome in Saudi Arabian teenagers, as well as to establish the length of phone use among these patients in order to evaluate whether it was connected to the emergence of De Quervain’s tenosynovitis. Methodology: This cross-sectional observational study was conducted among teenagers in Saudi Arabia studying in public and private schools. Most of the inquiries were closed-ended and sought information regarding the students’ use of various mobile phone sizes, regular text messaging, discomfort in the wrist or thumb, swelling or a snapping sound over the thumb, and limitations or pain aggravation when handling various objects. Results: The total number of teenagers that participated in the study was 200; 111 (55.5%) of them were males, while the remaining 89 (44.5%) were females. Out of 200 participants, 135 (67.5%) tested positive for Finkelstein disease; of these, 21 (15.5%) used smartphones for under 4 hours, 53 (39.2%) used smartphones for 5–7 hours, and 21 (15.5%) used smartphones more than 10 hours with P value of 0.008, which is significant and hence concluded that duration of using mobile phones had impact on De Quervain’s disease. Conclusion: In conclusion, Finkelstein’s sign, a marker that De Quervain’s illness is widespread, was present in 67.5% of the patients. Current findings suggest that De Quervain cannot be completely ruled out because of this population’s propensity to develop it.